Reference values for spirometric parameters in healthy children living in a Colombian city located at 2640 m altitude. Issue 6 (8th April 2019) - Aristizabal‐Duque, Ricardo; Castiblanco, Edwin; Rodriguez, Ingrid; Sossa‐Briceño, Monica P.; Rodriguez‐Martinez, Carlos E.
Abstract: Objectives: To identify the spirometric equations that are most appropriate for use in children and adolescents living in Bogota, Colombia after evaluating a set of relevant previously‐developed equations, including the Global Lung Function Initiative (GLI) 2012 spirometry reference equations. Methods: Healthy children aged between 6 and 17 years that were attending two randomly‐selected schools in Bogota were invited to participate in the study, from January 2017 to January 2018. All participants underwent spirometry, following the procedures recommended by the American Thoracic Society/European Respiratory Society (ATS/ERS) Task Force. To identify the model or group of models that best predict each spirometric parameter in our population, we performed extensive residuals analyses and constructed Bland‐Altman plots. Results: Three hundred twenty‐six spirometric tests (149 boys, 177 girls) formed the reference data set. Knudson and GLI‐2012 spirometry reference equations proved to be the most accurate in predicting the majority of spirometry parameters in both sexes and both age groups, each providing the lowest median prediction error in the residual analyses or the narrowest limits of agreement in the Bland‐Altman plots in approximately one‐third of the spirometry parameters analyzed. Conclusion: For the majority of spirometry parameters, we recommend the use of Knudson and GLI‐2012 spirometry reference equations for evaluating the respiratory function of children living in Bogota, Colombia, a city located at an altitude of 2640 m. Future investigations should target additional spirometric equations from Latin American populations living at moderate to high altitude to improve the GLI‐2012 equations.